PENDAMPINGAN MANAJEMEN DAN TATA KELOLA MASJID SERTA LEMBAGA AMIL ZAKAT INFAK DAN SODAQOH - Hafiez Sofyani (Jurnal Pengabdian UntukMu NegeRI, 2018)
The partners that invited to collaborate in community partnership activities are the Taqarrub Mosque Takis 1 Takmir and An-Nur Dusun Pakis 2 Mosque, and the Dlingo Village Head, Bantul Regency, Yogyakarta Special Region. The management of mosques and zakat through the Amil Zakat, Infak and Shodaqoh Institutions (LAZIS) at partner sites is still held traditionally and is not well organized. As a result of this, there was a community conflict triggered by the lack of transparency in the management of mosque finance and zakat. This is due to the level of understanding and competence of the Takmir Mosque which is a citizen of Pakis 1 and 2 which is inadequate. From this problem, a solution was proposed in the form of training and management assistance and governance of mosques and amil zakat infak and sodaqoh institutions. These activities include: drafting the bylaws, organizational structure, procurement of modules, guidelines, guidelines, and standard operating procedures for mosque management and LAZIS. From the results of the implementation of this program, it was concluded that there had been an increase in the quality of management and governance of the Taqarrub Mosque in Pakis 1 Hamlet and An-Nur mosque in Pakis 2, namely to be better and transparent. Conflicts related to bad prejudice arising from a small portion of the community regarding the management of mosque finance and LAZ can also be minimized.